Professional prospect in Mexico, a limited stage for college students - Gavotto-Nogales, Omar Iván (2015)
The aim of the study is to compare the employment landscape in Mexico and the feasibility to get a job in the professional field, after university studies. From a critical perspective it is stated that the cost-benefit makes it impossible to sustain policies and strategies that have been the subject of education in Mexico, however, the private sector in this area is promoted, which can be a factor that facilitates college entrance but can also limit access to this level. Thurow’s theory is the most appropriate one to explain the problem of unemployment that exists and an overpopulation of professionals, since the investment in human capital is not enough to get a job, if you do not have the relevant and sufficient labor supply. It is concluded that the professional scene in Mexico, represents a limited scenario for college students, based on the following arguments: a) 75% of unemployed in Mexico is represented by people with university degrees; b) Most busy professionals or employees are engaged in activities that do not correspond to their profession; c) Investment in human capital does not represent an economic recovery in the short-term for many professionals; d) The population of school-age young college increases each year, however, public universities are unable to facilitate entry to all applicants.